PEGylation of Deferoxamine for Improving the Stability, Cytotoxicity, and Iron-Overload in an Experimental Stroke Model in Rats - Xu, Jiake; Sun, Tong; Zhong, Rui; You, Chao; Tian, Meng (Frontiers in Bioengineering and Biotechnology, 2020)
Deferoxamine (DFO) is a widely used drug for the treatment of iron-overload-related diseases in the clinic. However, its inherent shortcomings, such as a short plasma half-life and cytotoxicity, need to be addressed to widen its clinical utility. In this study, PEGylated DFO was first synthesized, and its chemical structure was characterized, and then in vitro and in vivo studies were performed. The metabolism assay showed that the stability of the PEGylated DFO was significantly improved, with a half-life 20 times greater than DFO. Furthermore, the PEGylated DFO exhibited significantly lower cytotoxicity compared with DFO. Additionally, the hemocompatibility assay showed that the PEGylated DFO had no significant effect on the coagulation system, red blood cells, complement, and platelets. In vivo studies indicated that PEGylated DFO was capable of reducing the iron accumulation, degeneration of neurons, and promotion of functional recovery. Taken together, PEGylated DFO improved stability, cytotoxicity, and iron-overload in an experimental stroke model in rats, making it a promising therapy for treating iron-overload conditions in the clinic.